Has the Corporate Culture of State-Owned Enterprises Changed after Privatization? - Angga Erlando, Dwi Budi Santoso, Anorti Ika Wijaya, (Opción, 2019)
The objective of research is to examine factors of corporate culture that affect the performance of state-owned Indonesian enterprises (BUMN) after privatization. Structural Equation Model is applied in this research. Results suggest that three components of corporate culture, which are community, safety, and teamwork, have most significantly influence BUMN performance indicated by the highest share price, sales level, and profit rate. In conclusion, improvement in BUMN performance after privatization is mainly caused by an improvement in tangible assets such as a rise in cash to reduce debt, and no improvement in intangible assets for instance in innovation and labor productivity.